Apportionment of the sources of high fine particulate matter concentration events in a developing aerotropolis in Taoyuan, Taiwan. (July 2016) - Chuang, Ming-Tung; Chen, Yu-Chieh; Lee, Chung-Te; Cheng, Chung-Hao; Tsai, Yu-Jen; Chang, Shih-Yu; Su, Zhen-Sen
Abstract: To investigate the characteristics and contributions of the sources of fine particulate matter with a size of up to 2.5 μm (PM2.5 ) during the period when pollution events could easily occur in Taoyuan aerotropolis, Taiwan, this study conducted sampling at three-day intervals from September 2014 to January 2015. Based on the mass concentration of PM2.5, the sampling days were classified into high PM2.5 concentration event days (PM2.5 >35 μg m −3 ) and non-event days (PM2.5 <35 μg m −3 ). In addition, the chemical species, including water-soluble inorganic ions, carbonaceous components, and metal elements, were analyzed. The sources of pollution and their contributions were estimated using the positive matrix factorization (PMF) model. Furthermore, the effect of the weather type on the measurement results was also explored based on wind field conditions. The mass fractions of Cl − and NO3 − increased when a high PM2.5 concentration event occurred, and they were also higher under local emitted conditions than under long range transported conditions, indicating that secondary nitrate aerosols were the major increasing local species that caused high PM2.5 concentration events. Seven sources of pollution could be distinguished using the PMF model on the basis of the characteristics of the species. Industrial emissions, coal combustion/urban waste incineration, and local emissions from diesel/gasoline vehicles were the main sources that contributed to pollution on high PM2.5 concentration event days. In order to reduction of high PM2.5 concentration events, the control of diesel and gasoline vehicle emission is important and should be given priority. Highlights: The mass fractions of NH4 +, K +, Cl − and NO3 − increased during PM2.5 event days. Reduction of coal combustion/urban waste incineration emissions should be prioritized. The control of vehicle emission is important in the locally emitted periods. Secondary sulfate was mainly dominated by long-range transport. Abstract : On the basis of chemical composition measurements and source apportionment, the priority of source reduction in PM2.5 was determined in a developing aerotropolis.